2016
DOI: 10.3389/fphar.2016.00481
|View full text |Cite
|
Sign up to set email alerts
|

Silymarin Protects Mouse Liver and Kidney from Thioacetamide Induced Toxicity by Scavenging Reactive Oxygen Species and Activating PI3K-Akt Pathway

Abstract: Silymarin (SMN) has been shown to possess a wide range of biological and pharmacological effects. Besides, SMN has antioxidant and free radical scavenging activities. Thioacetamide (TAA) is a well-documented liver toxin that requires oxidative bioactivation to elicit its hepatotoxic effect which ultimately modifies amine-lipids and proteins. Our study has been designed in a TAA exposed mouse model to investigate whether SMN could protect TAA-induced oxidative stress mediated hepatic and renal damage. Results s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 65 publications
5
41
0
Order By: Relevance
“…Paraquat causes impaired renal function which is accompanied by reduction of the renal clearance rate and increasing of paraquat level, toxicity, and other organ dysfunctions (6,7). Administration of thioacetamide has been shown to induce liver and kidney injuries and silymarin ameliorated some parameters such as DNA fragmentation, nitric oxide, oxidative stress, collagen content, and liver and kidney histopathological changes in thioacetamide-induced toxicity (8). Silymarin is a potent antioxidant that can scavenge free radicals and ROS (9).…”
Section: Introductionmentioning
confidence: 99%
“…Paraquat causes impaired renal function which is accompanied by reduction of the renal clearance rate and increasing of paraquat level, toxicity, and other organ dysfunctions (6,7). Administration of thioacetamide has been shown to induce liver and kidney injuries and silymarin ameliorated some parameters such as DNA fragmentation, nitric oxide, oxidative stress, collagen content, and liver and kidney histopathological changes in thioacetamide-induced toxicity (8). Silymarin is a potent antioxidant that can scavenge free radicals and ROS (9).…”
Section: Introductionmentioning
confidence: 99%
“…The findings suggested that HE/DA/M nano-micelles showed specificity to be accumulated in tumor tissues. Additionally, the toxicity of HE/DA/M formulation in vivo was investigated through assessing essential hepatic and renal health indexes [26,30,66,67]. AST, ALT, BUN and CREA contents in mice with treatment of HE/DA/M nano-micelles were similar to that in the Con group, indicating that HE/DA/M nano-micelles caused no severe hepatic and kidney toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…Al-Attar et al studied the protective effects of olive leaf extract on nephrotoxicity of this substance in the kidneys of mice and proved that the levels of urea and serum creatinine in the group treated with olive leaf extract reduced, but not significantly. In terms of histological, the normality of the kidney structure was proved in the group treated with the extract (24,25).…”
Section: Thioacetamidementioning
confidence: 93%
“…Thioacetamide can be viewed as a hepatic toxin and carcinogen (24). The toxic complications of this compound are not only limited to the liver, but involve several organs such as the kidneys, spleen, lungs, intestines, and brain (24,25).…”
Section: Thioacetamidementioning
confidence: 99%
See 1 more Smart Citation